Usage of licks for guitarist in enhancing improvisation in jazz music / Muhammad Indra Hidayat Rosli and Muhammad Talha Rusli - Rosli, Muhammad Indra Hidayat; Rusli, Muhammad Talha (2019)
Every guitarist interpreting their solo in different way and dream to deliver their music well during a performance. This research examines how do guitarists interpreting usage of licks in enhancing improvisation in jazz music.